Laser polarizado versus campo elétrico uniforme em cultura celular: efeitos biológico e biofísico - Lopes, Fabio (2018)
Currently, photobiomodulation is one of the most commonly used non-invasive therapies, and its benefits in wound healing are well described by literature. However, the dosimetric parameters of photobiomodulation, such as direction of polarization, coherence and regime of operation, are rarely considered. Although the radiation emitted by a laser is electromagnetic and, in turn, there is an associated electric field, the intensity of the electric field and its direction of propagation are not properly discussed. The objectives of this research were: developing a device capable of creating an electric field of the same intensity as that created by a polarized red laser; comparing cell migration and alignment of human fibroblasts produced by linearly polarized photobiomodulation to migration and alignment triggered by an electric field of the same intensity using the created device. The cells were sown in cover slots and submitted to the wound test, then divided into five experimental groups according to the received treatment: Control (C), parallel electric field (E //) and perpendicular electric field (Epp) in relation to the wound, laser polarized parallel to the wound (L //) and perpendicularly (Lpp) to the wound. All groups, except for the control group, were submitted to the electric field of 2V / cm intensity for 100 seconds by means of the polarized laser (λ = 660 nm) or a non-electromagnetic source. Migration was evaluated after 12 hours of treatment and alignment after 6 and 12 hours. All the treatments were effective in cell migration, with the L // group presenting the best rate. As for the alignment, 6 hours after the application of the electric field the control group was the least aligned and the L // was the only one aligned parallel to the incident field, in addition to being more aligned in relation to the others (p <0.05). 12 hours after the application of the electric field there was no group aligned parallel to the incident field and the control group was not different from E //. The most aligned group, Epp, although perpendicular to the incident electric field, was no different from the Lpp group. The direction of vibration of the electric field of the laser, when parallel to the long axis of the wound provoked in a culture of fibroblasts, looks promising for migration after 12 hours, but in that same period the best cellular alignment was verified with the perpendicular direction of the electric field of the non-laser device.